Biotin, a universal and essential cofactor: synthesis, ligation and regulation - Chaiyos Sirithanakorn; John E. Cronan (FEMS Microbiology Reviews, 2021)
Biotin is a covalently attached enzyme cofactor required for intermediary metabolism in all three domains of life. Several important human pathogens (e.g. Mycobacterium tuberculosis) require biotin synthesis for pathogenesis. Humans lack a biotin synthetic pathway hence bacterial biotin synthesis is a prime target for new therapeutic agents. The biotin synthetic pathway is readily divided into early and late segments. Although pimelate, a 7-carbon α,ω-dicarboxylic acid that contributes 7 of the 10 biotin carbons atoms, was long known to be a biotin precursor, its biosynthetic pathway was a mystery until the Escherichia colipathway was discovered in 2010. Since then, diverse bacteria encode evolutionarily distinct enzymes that replace enzymes in the E. coli pathway. Two new bacterial pimelate synthesis pathways have been elucidated. In contrast to the early pathway, the late pathway, assembly of the fused rings of the cofactor, was long thought settled. However, a new enzyme that bypasses a canonical enzyme was recently discovered as well as homologs of another canonical enzyme that functions in synthesis of another protein-bound coenzyme, lipoic acid. Most bacteria tightly regulate transcription of the biotin synthetic genes in a biotin-responsive manner. The bifunctional biotin ligases which catalyze attachment of biotin to its cognate enzymes and repress biotin gene transcription are best understood regulatory system.
Keywords: Biotin and Related Studies; Click Chemistry and Applications; Biochemical and Molecular Research